Effects of operating parameters for dry reforming of methane : A short review - Muhammad, Ayoub; Chong, Chi Cheng; Asif, Zamir; Cheng, Yoke Wang; Farrukh, Sarah; Naqvi, Salman Raza; Herma Dina, Setiabudi; Riaz, Nadia; Ramzan, Naveed (EDP Sciences, 2021)
Dry reforming of methane (DRM) which also known as CO2 reforming of methane is a well-investigated reaction to serve as an alternative technique to attenuate the abundance of greenhouse gases (CO2 and CH4). The syngas yielded is the main component for the liquid fuels and chemicals production in parallel with the fluctuating price of oil. Major researches were executed to seek for the well-suited catalysts before the commercialization of DRM can be realized. However, severe deactivation due to the carbon formation restricted the usage of promising Ni-based catalysts for DRM. Meanwhile, the deactivation on these catalysts can be associated with the operating conditions of DRM, which subsequently promoted the secondary reactions at different operating conditions. In fact, the parametric study could provide a benchmark for better understanding of the fundamental steps embodied in the CH4 and CO2 activation as well as their conversions. This review explores on the influences of the reaction operating parameters in term of the reaction temperatures, reactant partial pressures, feed ratios, and weight hourly space velocity (WHSV) on catalytic performance and carbon accumulation for the DRM.